Terapi komplementer pasien kanker yang menjalani kemoterapi: A literature review - Zulfitrah Romadiansyah; Sri Wahyuni (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Complementary therapy is part of a nursing intervention that is simple and has no side effects but provides great benefits for cancer patients who experience side effects from chemotherapy treatment that cancer patients undergo. Purpose: To determine and analyze complementary therapies that can be applied to cancer patients undergoing chemotherapy. Method: Literature review search from various online databases from 2018-2023, namely Google Scholar, Pubmed, and ScienceDirect, with the search keywords